Coronary angiography after out-of-hospital cardiac arrest without ST-segment elevation: one-year outcomes of a randomized clinical trial - Desch, Steffen; Freund, Anne; Akın, Ibrahim; Behnes, Michael; Preusch, Michael; Zelniker, Thomas; Skurk, Carsten; Landmesser, Ulf; Graf, Tobias; Eitel, Ingo; Fuernau, Georg; Haake, Hendrik; et al. (JAMA cardiology, 2023)
Myocardial infarction is a frequent cause of out-of-hospital cardiac arrest (OHCA). The long-term effect of early coronary angiography on patients with OHCA with possible coronary trigger but no ST-segment elevation remains unclear.To compare the clinical outcomes of early unselective angiography with the clinical outcomes of a delayed or selective approach for successfully resuscitated patients with OHCA of presumed cardiac origin without ST-segment elevation at 1-year follow-up.The TOMAHAWK trial was a multicenter, international (Germany and Denmark), investigator-initiated, open-label, randomized clinical trial enrolling 554 patients between November 23, 2016, to September 20, 2019. Patients with stable return of spontaneous circulation after OHCA of presumed cardiac origin but without ST-segment elevation on the postresuscitation electrocardiogram were eligible for inclusion. A total of 554 patients were randomized to either immediate coronary angiography after hospital admission or an initial intensive care assessment with delayed or selective angiography after a minimum of 24 hours. All 554 patients were included in survival analyses during the follow-up period of 1 year. Secondary clinical outcomes were assessed only for participants alive at 1 year to account for the competing risk of death.Early vs delayed or selective coronary angiography and revascularization if indicated.Evaluations in this secondary analysis included all-cause mortality after 1 year, as well as severe neurologic deficit, myocardial infarction, and rehospitalization for congestive heart failure in survivors at 1 year.A total of 281 patients were randomized to the immediate angiography group and 273 to the delayed or selective group, with a median age of 70 years (IQR, 60-78 years). A total of 369 of 530 patients (69.6%) were male, and 268 of 483 patients (55.5%) had a shockable arrest rhythm. At 1 year, all-cause mortality was 60.8% (161 of 265) in the immediate angiography group and 54.3% (144 of 265) in the delayed or selective angiography group without significant difference between the treatment strategies, trending toward an increase in mortality with immediate angiography (hazard ratio, 1.25; 95% CI, 0.99-1.57; P = .05). For patients surviving until 1 year, the rates of severe neurologic deficit, myocardial infarction, and rehospitalization for congestive heart failure were similar between the groups.This study found that a strategy of immediate coronary angiography does not provide clinical benefit compared with a delayed or selective invasive approach for patients 1 year after resuscitated OHCA of presumed coronary cause and without ST-segment elevation.ClinicalTrials.gov Identifier: NCT02750462
Gesehen am 01.08.2024